Student-factor as determinants of student pastors’ attitude, perception and motivation to use icts for learning of languages in Baptist College of Theology, Lagos (2019)
This study examined student-pastors’ attitude, perception and motivation to use Information and Communication Technology (ICT) for the teaching and learning of languages in theological institutions. Forty- six (46) 100, 200. 300 and 400 levels student-pastors selected by purposive random sampling from the Theology, Religious Education, and Church Music Departments of Baptist College of Theology, Lagos participated in the study. Teaching and Learning Languages Questionnaires (TLLQ) was used to collect data in order to test four null hypotheses at p<. 05 level of significance. Data collected were analysed using descriptive statistics, analysis of variance (ANOVA) and t-test. Findings indicated that there is no significant difference in the student pastors’ perception, motivation and attitude to the use of instructional software in learning languages across subject areas, gender, age and levels of study